Functioning And Family Repercussion In Pregnant Adolescents Cared In The National Maternal Perinatal Institute Period Of Time January – March 2013. - Alegría, Nelly Ojeda (2019)
Objective. To Characterize, from a family approach adolescents who are cared in the Instituto Nacional Materno Parinatal. Materials and methods. The universe studied embraced all the adolescents hospitalized in the service of obstetrics and gynecology of adolescence, during the period of time from January to March 2011. It analyzed the social reports, psychological and medical histories of the clinic. They were studied the variables age, level of education, origin, marital status, occupation, age of the couple, occupation of the couple, couple’s relationship, No. of sexual couples, No. of siblings, occupation of the father, occupation of the mother, classification of the family, family functioning, No. of brothers, protective factors, emotional link, clinical care, health